2009
DOI: 10.1016/j.jog.2009.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Gravity field variations from superconducting gravimeters for GRACE validation

Abstract: The network of superconducting gravimeters (SG) of the 'Global Geodynamics Project' (GGP) offers the unique opportunity to supplement and validate the gravity field variations derived from the GRACE satellite mission. Because of the different spatial and temporal resolution of the gravity data a combination of all data sets can be used to retrieve a maximum of information regarding mass transfers especially related to hydrology which is deployable as constraint for hydrological modelling.For a consistent combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…For filter lengths of about 1000 km, closest correspondence to the SG gravity residuals is obtained. This is in accordance with the results published previously by Hinderer et al (2006), Neumeyer et al (2006b, and Weise et al (2009). It is interesting that it is necessary to apply rather strong filters in order to make time series derived from GRACE observations comparable with the corresponding time series based on SG.…”
Section: Comparison Of Grace Gravity Variations Against Sg Observationssupporting
confidence: 91%
See 3 more Smart Citations
“…For filter lengths of about 1000 km, closest correspondence to the SG gravity residuals is obtained. This is in accordance with the results published previously by Hinderer et al (2006), Neumeyer et al (2006b, and Weise et al (2009). It is interesting that it is necessary to apply rather strong filters in order to make time series derived from GRACE observations comparable with the corresponding time series based on SG.…”
Section: Comparison Of Grace Gravity Variations Against Sg Observationssupporting
confidence: 91%
“…The close-up range of 1 km around the station has not been considered here. With respect to the interim comparison for three stations in Weise et al (2009), the general agreement in the seasonal signals is confirmed by the three additional European SG stations, with maximum signal amplitudes in winter/spring and minimum signal amplitudes at the end of summer. The SG time series at the Moxa, Strasbourg, Vienna, and Wettzell sites were reduced for the local hydrological effect, taking into account the individual local station conditions (Section 2).…”
Section: Comparison Of Terrestrial and Satellite-derived Gravity Fielmentioning
confidence: 55%
See 2 more Smart Citations
“…A comparison between the terrestrial gravity data from Moxa station, GRACE satellite-derived gravity field variations for a Gauss filtering with fl = 10 and fl = 13, respectively (Neumeyer et al 2006(Neumeyer et al , 2008Weise et al 2009), and gravity changes based on the Water-GAP Global Hydrology Model (WGHM) (Döll et al 2003) is given in Fig. 12(b).…”
Section: Large-scale Considerationsmentioning
confidence: 99%